Infertile environments: epigenetic toxicology and the reproductive health of Chinese men - Lamoreaux, Janelle (Critical global health., 2022)
"In Infertile Environments, Janelle Lamoreaux investigates how epigenetic research into the effects of toxic exposure conceptualizes and configures environments. Drawing on fieldwork in a Nanjing, China, toxicology lab that studies the influence of pesticides and other pollutants on male reproductive and developmental health, Lamoreaux shows how the lab's everyday research practices bring national, hormonal, dietary, maternal, and laboratory environments into being. She situates the lab's work within broader Chinese history as well as the contemporary cultural and political moment, in which declining fertility rates and reproductive governance and technology are growing concerns. She also points to how toxicology in China is a transnational endeavor tied to both local conditions and international research agendas and infrastructures, which highlights the myriad scales and scope of epigenetic environments. At a moment of growing concerns about toxins, endocrine disrupting chemicals, and climate change, Lamoreaux demonstrates that epigenetic research's proliferation of environments produces new kinds of toxic relations that impact multiple generations of humans."--